ETHYLCELLULOSE FLOATING MICROSPHERES OF ANTIDIABETIC AGENT: IN VITRO AND IN VIVO EVALUATION - Kohli, Seema; Sharma, Megha; Pal, Abhisek (International Journal of Applied Pharmaceutics, 2016)
Objective: To develop and evaluate floating type gastro-retentive dosage form, appropriate for controlled release of repaglinide (RG) having a narrow therapeutic window. Methods: Repaglinide loaded microspheres (MS) using biological macromolecule ethylcellulose (EC) was prepared by a solvent diffusion-evaporation technique using polyvinyl alcohol (PVA) emulsifier. Compatibility of drug and polymer was studied by Fourier-transform infrared spectroscopy (FTIR). During formulation, various process optimisation parameters studied were stirring speed, the concentration of drug, polymer and emulsifier. Characterization and in vitro evaluation was performed. In vivo antidiabetic activity was performed on alloxan induced diabetic rats followed by histopathological screening. Results: The average particle size was in the range of 174-243 Âµm. Yield, entrapment and buoyancy of microspheres were 68.4ÂÂ-79.8, 58.6-73.1 and 71.8-84.1% respectively. 65.1% release of drug from optimised formulation was obtained which follows first-order kinetics (r2 = 0.989). Optimised formulation treated group shows significant (p<0.01) decrease in glucose level of blood as compared to pure drug treated group during the later hours of study with satisfactory results of histology. Conclusion: The investigation revealed the promising potential of gastro retentive microspheres for delivering RG for the treatment of non-insulin dependent diabetes mellitus (NIDDM).